The Political Theory of Judith N. Shklar Exile from Exile - Hess, A. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Judith Shklar called for a radical shift in political theory, toward a view of the history of ideas through the lens of exile. Hess takes this lens and applies it to Shklar's own life and theoretical work.